The essence of the information technology paradigm of education - Gunay Muslim gızı Nazarova (World Scientific Reports, 2024)
The article talks about the development of technological progress and the increase of general knowledge of humanity in the modern era, the intensive interaction of human knowledge and information of the information society, and the role of the information technology paradigm of education in the formation of the socio-cultural environment of the processes of informatization of education. In the national education system of the Republic of Azerbaijan, more effective ways of traditional information technologies and the most important areas of education informatization are shown in all types of activities. The current state of the education system reflects the contradictions between, on the one hand, the increasing demands on public and individual intelligence, consciousness and spirituality, human design and forecasting ability, and on the other hand, the actual level of the quality of education. The philosophical-methodological basis of the new educational paradigm is analyzed by modern philosophy, pedagogy and the methodology of the latest integrative scientific directions.